145 Implementing Vorasidenib in Clinical Practice: A Single-Centre Real-World Service Evaluation - Brooke Smart; Lorna Raymond; Antonia Creak; Liam Welsh; Ella Nicklin; Matteo Isolani; Ozofu Omuemu; Francesca Solda; Nicola Rosenfelder (Neuro-Oncology, 2026)
Abstract Introduction The phase 3 INDIGO trial demonstrated significantly improved progression-free survival with Vorasidenib in patients with residual/recurrent IDH-mutant grade 2 oligodendroglioma and astrocytoma, supporting its integration into routine neuro-oncology practice. We undertook a real-world service evaluation at the Royal Marsden Hospital to assess toxicity, monitoring burden, and implications for wider UK implementation ahead of the anticipated appraisal by the National Institute for Health and Care Excellence (NICE). Methods We performed a retrospective evaluation of adults treated with vorasidenib within a Managed Access Programme (MAP) between April 2024 and September 2025. Eligible patients had predominantly non-enhancing IDH-mutant grade 2–3 glioma, prior surgery, no previous chemotherapy/radiotherapy, and satisfactory baseline liver function tests (LFTs). LFT monitoring and dose adjustments adhered to MAP guidelines. Results Forty-four patients commenced treatment; four discontinued (two Grade 4 toxicities, one Grade 3 toxicity, one progression) and one transferred care, leaving 39 patients on treatment at data cut-off (01/12/2025). Median treatment exposure was 10 cycles. Histology comprised astrocytoma (n = 22; eighteen Grade 2, four Grade 3) and oligodendroglioma (n = 22; seventeen Grade 2, one Grade 2/3, four Grade 3). Transaminitis occurred in 82%; Grade ≥3 events were observed in 4/44 patients. First events most commonly occurred during cycle 1 (43%) and declined thereafter. A total of 513 clinic appointments were delivered during cycles 1–6, representing a 59% increase over the minimum monitoring schedule recommended in the Summary of Product Characteristics, with the largest increases in cycles 3 (129%) and 4 (108%). Conclusion Vorasidenib is generally well tolerated and conveniently administered once daily. However, hepatotoxicity requires proactive monitoring with significant service implications. NHS implementation will require optimised neuro-oncology pathways, including protocol-driven care, selective remote review, and multidisciplinary coordination.